Amniotic fluid volume as a predictor of fetal distress in intrauterine growth retardation - Tongsong T. (2014)
To determine the efficacy of sonographic assessment of amniotic fluid volume (AFV) in predicting intrapartum fetal distress in pregnancies with intrauterine growth retardation (IUGR) compared with the nonstress test (NST).